2020
DOI: 10.3389/fphar.2020.01287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Doses of Eucalyptus Oil From Eucalyptus globulus Labill on Respiratory Tract Immunity and Immune Function in Healthy Rats

Abstract: Eucalyptol (1,8-cineole), the major constituent of eucalyptus oil (EO), was used in traditional medicine as a remedy for colds and bronchitis. This study aimed at clarifying the effect of eucalyptol on respiratory immune function of CD8 and CD4 cells, and alveolar macrophages (AM). Thirty male Sprague-Dawley rats were divided into experimental and control groups. The drug was given once a day for 3 weeks and the experimental group was divided according to the eucalyptol dose into: 30, 100, and 300 mg•kg-1 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
(42 reference statements)
1
18
0
1
Order By: Relevance
“…and Zea mays L. E. globulus is one of the most widely planted hardwood tree species in temperate regions of the world, mostly used as raw material for pulp and paper industry due to its highquality cellulose pulp, low lignin, and lipid content (Aumond et al, 2017). This species is also used for the production of essential oils in the pharmaceutical industry (Shao et al, 2020). Notably, E. globulus has been successfully grown in a broad range of environmental conditions, and it stands out as the targets of multiple breeding programs to improve economically important traits such as tree growth and wood quality (Ballesta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…and Zea mays L. E. globulus is one of the most widely planted hardwood tree species in temperate regions of the world, mostly used as raw material for pulp and paper industry due to its highquality cellulose pulp, low lignin, and lipid content (Aumond et al, 2017). This species is also used for the production of essential oils in the pharmaceutical industry (Shao et al, 2020). Notably, E. globulus has been successfully grown in a broad range of environmental conditions, and it stands out as the targets of multiple breeding programs to improve economically important traits such as tree growth and wood quality (Ballesta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, some investigators attributed the EO anti-inflammatory activity to the presence of monoterpenes, namely 1,8-cineole, which is a potent suppressor of cytokine release [ 48 ]. Nevertheless, it is important to take into consideration a study reporting that a high concentration of EO (hence, 1,8-cineole) affects the immune function in the respiratory tract and the overall organism immunity in rats, while a low concentration can have the opposite effect [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that ZMD had a stronger antioxidant and anti‐inflammatory than CMD (Li et al., 2016; Zhao et al., 2017), and better immunomodulatory activities (Lu et al., 2017) than CMD. Studies based on eucalyptus oil found eucalyptus oil has antioxidant, antibacterial, antifungal properties, and immunoregulatory function (Boukhatem et al., 2020; Shao et al., 2020). The linalool and 1,8‐cineole inhibited non‐small cell lung cancer A549 cell migration (Rodenak‐Kladniew et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Studies based on eucalyptus oil found eucalyptus oil has antioxidant, antibacterial, antifungal properties, and immunoregulatory function (Boukhatem et al, 2020;Shao et al, 2020). The linalool and 1,8-cineole inhibited non-small cell lung cancer A549 cell migration (Rodenak-Kladniew et al, 2020).…”
Section: Selection Of Representative Signal Peaksmentioning
confidence: 99%